Juridical review of moral rights ownership in copyright of photographic works used for artificial intelligence algorithms - Rahmawan, Triya Indra; Amrulla, Mohammad Fahrial; Sunarjo, Sunarjo (Jurnal Penelitian, 2023)
This research delves into the legal landscape concerning moral rights ownership within the realm of copyright for photographic works, specifically exploring their utilization within artificial intelligence (AI) algorithms. Focusing on the intersection of intellectual property law and AI technology, the study investigates the rights and protections accorded to creators of photographic works under copyright laws. The analysis encompasses the ethical and legal considerations pertaining to the use of these works in AI algorithms, scrutinizing issues related to attribution, integrity, and the recognition of creators. By examining the current legislative frameworks and jurisprudence, this research aims to provide insights into the challenges, implications, and potential regulatory adaptations required to ensure the preservation of moral rights for creators within the context of AI-utilized photographic works. The results of this research found that copyright and moral issues in photographic works used in AI are areas that require deeper legal clarification and are responsive to technological developments. It should consider protecting traditional creators' rights while adjusting the definition and protection of rights for AI-generated works to maintain a fair balance between the rights of creators, users, and technological progress.